1991
DOI: 10.1007/bf01756594
|View full text |Cite
|
Sign up to set email alerts
|

In situ activation of syngeneic tumour-specific cytotoxic T lymphocytes: Intra-pinna immunization followed by restimulation in the peritoneal cavity

Abstract: Tumour-specific cytotoxic T lymphocytes (CTL) are usually obtained after immunization in vivo and restimulation of immune cells in vitro. We here describe the generation of syngeneic tumour-specific CTL within no more than 9 days by priming and restimulation in vivo. This is achieved only if the correct sites are used both for primary immunization (ear pinna) and for restimulation (peritoneal cavity). The kinetics of immune T cell induction and of the secondary response in vivo will be reported. While a second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Tumour iPEC 14 were obtained and adoptive transfer experiments were performed as previously described 16 . Briefly, naïve DBA/2 mice were primed with 5 × 10 4 live ESbL‐Gal at a non‐tumorigenic site, the ear pinna (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumour iPEC 14 were obtained and adoptive transfer experiments were performed as previously described 16 . Briefly, naïve DBA/2 mice were primed with 5 × 10 4 live ESbL‐Gal at a non‐tumorigenic site, the ear pinna (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 In the present study, the immunization protocol involved live replication competent tumour cells for priming 13 and a replication-incompetent c-irradiated tumour cell vaccine for boosting and attraction of TAA-specific immune cells to the peritoneal cavity. [14][15][16] This protocol has been demonstrated to result in tumour protection and long-term survival of the animals, and to induce a primary CD8 + T-cell response 3,17 as well as a tumour dormancy state in the bone marrow microenvironment. 18,19 As the intraperitoneal (i.p.)…”
Section: Introductionmentioning
confidence: 99%
“…To this aim we have employed the well-characterized L5178 lymphoma line Eb, which expresses characteristic Kd-associated tumor antigens and elicits specific cytotoxic T-cell responses in immunized or tumor-bearing syngeneic hosts (7)(8)(9). Vaccination of syngeneic DBA/2 mice with live tumor cells was achieved either through local secretion of interleukin 4 (1L4), which is known to render tumor cells nontumorigenic (10,11), or through the inoculation of viable parental Eb cells into a site refractory to the growth of these cells [intra-ear pinna (i.e.)].…”
mentioning
confidence: 99%
“…27 In the immunization studies, it was observed that the ear pinna appeared to be a privileged site for induction of the host antitumor immune response, perhaps due to the concentration of Ag-presenting cells (i.e., Langerhans cells). 28 Our observations that IFN-producing ESb tumor cells grew poorly following s.c. inoculation, whereas the same cells were as tumorigenic as the parental ESb cells following i.v. injection, suggest that the secretion of IFN-␣, associated with tumor Ag at the s.c. site of tumor growth, acts as a strong signal for the recruitment and activation of Ag-presenting cells, such as macrophages, which may then stimulate a T-cell-mediated antitumor response.…”
Section: Discussionmentioning
confidence: 76%